2021
DOI: 10.4081/monaldi.2021.2027
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of interstitial lung diseases and their association with pulmonary hypertension

Abstract: Interstitial lung diseases (ILDs) are an intriguing group of pulmonary disorders, which still require the study of epidemiological, genetic, pathophysiological, clinical, and radiological parameters. Pulmonary hypertension (PH) is an underreported complication in interstitial lung diseases which is associated with worse outcome. In our study, we have reported the spectrum of ILDs and estimated the prevalence of pulmonary hypertension among these subjects at a tertiary care centre. A cross-sectional study was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…[23,24] However, it should be kept in mind that bronchiectasis and ILD are on a spectrum with patients having mild and others having advanced disease. [25] Therefore, we cannot generalize this to each ILD and bronchiectasis patient.…”
Section: Discussionmentioning
confidence: 99%
“…[23,24] However, it should be kept in mind that bronchiectasis and ILD are on a spectrum with patients having mild and others having advanced disease. [25] Therefore, we cannot generalize this to each ILD and bronchiectasis patient.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, PH was confirmed by RHC in 44% in a cohort of 50 chronic hypersensitivity pneumonitis (HP) patients ( 9 ). A 2021 cross-sectional study performed at a tertiary care center in India, showed 46% of 239 ILD patients (32.2% HP, 31.4% CTD-ILD, 36.4% other ILD diseases) had screening echocardiograms suggestive of PH (mPAP estimate > 20 mm Hg) at the time of diagnosis ( 10 ). Patients with CPFE are especially susceptible to development of PH with a prevalence of 30–50% ( 11 ).…”
Section: Epidemiology: a Common Consortmentioning
confidence: 99%